Luna a novel - Peters, Julie Anne. (New York Little, Brown, 2006)
With the help of his sister, Liam secretly transforms himself into a girl when evening falls, but although he wants to present his female persona to the world, he fears the reaction of the rest of his family.
"Megan Tingley Books".
Reprint. Originally published: 2004.
"MT books"--Spine.
"Reading group guide inside"--P. [4] of cover.
Keywords: Transsexuals -- Fiction; Brothers and sisters -- Fiction; Identity (Philosophical concept) -- Fiction; Family problems -- Fiction